Stabilizing History through Statues, Monuments, and Memorials in Curzon's India. (March 2023) - Ghosh, Durba
Abstract: This article argues that projects to make Britain's imperial history visible to the public through the display of statues, the establishment of a history museum, and the renovation of historical markers solidified a colonial narrative about the British empire's permanence in India during the first two decades of the twentieth century, decades in which anticolonial unrest threatened the British occupation of the subcontinent. The monumental scale expressed permanence. An imperial aesthetic linked the cities important to showcasing the empire in Calcutta, New Delhi, and London. Contrary to mainstream assumptions that commemorations should be preserved for the sake of documenting history, these markers enacted a British story of triumph at a moment when mass campaigns against British rule were occurring. Coming at the end of a long nineteenth century of statue mania, when many European nations installed memorials to national heroes, the installation of monuments in India presented a colonialist public history of events such as the Black Hole incident of 1757 or the rebellions of 1857. Drawing from Viceroy George Curzon's ambitions in historical preservation and monumentalizing, the article shows how he stabilized a British narrative of India amid anticolonial campaigns of protest.